Influence of the Fe : Ni Ratio in FexNi9‐xS8 (x=3–6) on the CO2 Electroreduction. Issue 16 (18th August 2021) - Tetzlaff, David; Pellumbi, Kevinjeorjios; Puring, Kai junge; Siegmund, Daniel; Polet, Wigbert S. K.; Checinski, Marek P.; Apfel, Ulf‐Peter
Abstract: The electrochemical CO2 reduction (CO2 R) is a promising approach to decrease the amount of CO2 in the atmosphere by producing commodity chemicals or fuels using renewable energies. Herein, the development of non‐noble metal electrocatalysts is regarded as a key point for achieving the transition of CO2 R to industrial scales. Transition metal chalcogenides of the pentlandite structure (M9 X8 ) have emerged as promising electrocatalysts to produce syngas. In this line, we present the electrochemical CO2 R of Fex Ni9‐x S8 (x=3–6) with variable Fe : Ni ratios. All materials can reduce H2 O/CO2 mixtures to CO or H2 respectively with varying efficiency depending on the Fe : Ni ratio and the water content. While CO2 R in proton‐rich organic electrolytes was mainly accompanied by hydrogen evolution, the CO2 R activity climaxed with F.E. of 3.6 % for CO and 0.3 % for methane using Fe3 Ni6 S8 . Using electrolytes with low water content, CO production with F.E. close to 90 % was demonstrated. Counterintuitively, the variation of the Fe : Ni ratio led only to small alterations in the CO2 R activity. Quantum mechanical studies were performed to get further information on the observed trends and provide further insight into structure/activity relationships for the Fe/Ni pentlandite system and its CO2 R activity opening the path towards the development of more active and robust CO2 R electrocatalysts. Abstract : The electrocatalytic CO2 reduction by (Fe, Ni)9 S8 in an organic solvent yields different products depending on the catalyst composition and the water solvent content.